Infection control teams for reducing healthcare-associated infections in hospitals and other healthcare settings: a protocol for systematic review. Issue 3 (5th March 2021) - Thandar, Moe Moe; Matsuoka, Sadatoshi; Rahman, Obaidur; Ota, Erika; Baba, Toshiaki
Abstract : Introduction: Healthcare-associated infections (HCAIs) are a worldwide problem. Infection control in hospitals is usually implemented by an infection control team (ICT). Initially, ICTs consisted of doctors, nurses, epidemiologists and microbiologists; then, in the 1980s, the infection control link nurse (ICLN) system was introduced. ICTs (with or without the ICLN system) work to ensure the health and well-being of patients and healthcare professionals in hospitals and other healthcare settings, such as acute care clinics, community health centres and care homes. No previous study has reported the effects of ICTs on HCAIs. This systematic review aims to assess the effectiveness of ICTs with or without the ICLN system in reducing HCAIs in hospitals and other healthcare settings. Methods and analysis: We will perform a comprehensive literature search for randomised controlled trials in four databases: PubMed, Embase, CINAHL and the Cochrane Library. The primary outcomes are: patient-based/clinical outcomes (rate of HCAIs, death due to HCAIs and length of hospital stay) and staff-based/behavioural outcomes (compliance with infection control practices). The secondary outcomes include the costs to the healthcare system or patients due to extended lengths of stay. Following data extraction, we will assess the risk of bias by using the Cochrane Effective Practice and Organization of Care risk of bias tool. If data can be pooled across all the studies, we will perform a meta-analysis. Ethics and dissemination: We will use publicly available data, and therefore, ethical approval is not required for this systematic review. The findings will be submitted for publication in peer-reviewed journals. Trial registration number: CRD42020172173.